Study of Microorganism Growth Pattern in Nasal Pack of Patients Visiting the Department of ENT, Head and Neck Surgery - Shrestha, I.; Pokharel, M.; Dhakal, A.; Amatya, R.C.M.; Madhup, S.; Sherchan, J.B. (Kathmandu University Medical Journal, 2017)
Background Nasal packs are utilized nearly by otorhinolaryngologists for controlling epistaxis and post nasal procedures. Complications have been reported due to them; therefore the use of antibiotics is a common practice among otorhinolaryngologists. Objective To detect microbiological flora associated with nasal packing and find evidence to support the benefit of systemic antibiotics with it. Method A prospective, analytical study was conducted on 51 patients presenting to the Department of ENT, KUSMS from June to September 2015 who required nasal packing. Approval of the local Institutional review committee (IRC) was taken. The mid part of the pack was collected in a sterile bottle under aseptic technique and sent to microbiology department. Specimen collection, culture, identification tests were done according to the guidelines by American Society for Microbiology. Data were collected using the individual patient records and Microsoft Office Excel 2007. Statistical analysis was performed with SPSS 16.0. Result Among the 51 cultures; 33 (64.7%) were positive. In 18 (35.3%) cultures no organism was grown. Statistical analysis did not show significance between duration of pack kept with microbial growth (p=0.051) or the type of pack kept (p=0.212) .It showed significance with foul smell of the pack to the growth (p=<0.001). Conclusion Microbiological flora was associated with nasal pack. Antibiotic soaked nasal packs have lesser incidence of positive bacterial growth when compared with plain nasal packs. Nasal packs kept for less than 48 hours have lesser incidence of positive bacterial growth when compared with nasal packs kept for more than 48 hours. Therefore, administering systemic antibiotics in cases when we plan to keep the pack for longer duration is recommended.